If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 6forx = 13 Reorder the terms: 6forx + x = 13 Solving 6forx + x = 13 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1x' to each side of the equation. 6forx + x + -1x = 13 + -1x Combine like terms: x + -1x = 0 6forx + 0 = 13 + -1x 6forx = 13 + -1x Divide each side by '6orx'. f = 2.166666667o-1r-1x-1 + -0.1666666667o-1r-1 Simplifying f = 2.166666667o-1r-1x-1 + -0.1666666667o-1r-1 Reorder the terms: f = -0.1666666667o-1r-1 + 2.166666667o-1r-1x-1
| 120=p+7p | | 2x-3=-4+x | | 3x+(4x-1)=90 | | 0.1t=.4+.3t | | 8m+m=90 | | X+2x-1=2(-1+x) | | (4x^2-9x-9)= | | -x^2+515x-7500=0 | | 10x-45=3(b-15) | | h(t)=196-16t^2 | | x^2+515x-7500=0 | | -3n+3(5n-4)=8n-2(-8n+6) | | 6n+2n=96 | | 5x-(8x+4)=8x+-15 | | 2z+9z=4z+45+22 | | 5x(8x+4)=8x-15 | | -2(8r+2)-5(1-2r)=-r-3-4r | | 2n+2u=p | | 5(2+2x)=9(x-3) | | -2-5=7n | | 27-u=172 | | 6-2n=4n+4 | | (5x^2-11x+4)= | | x^2+545x-7500=0 | | -3(2-5m)=2(7m-5) | | 6-x=4x+21 | | -7=7.37802(x)+(-4.9)(x^2) | | 5t-2=34-t | | 125+10x=230+2x | | (2q-3)q=27 | | 12y+6=12y+7 | | 5x+28=x |